L’insegnamento della cortesia come elemento della competenza comunicativa nei manuali d’italiano LS: sfide e soluzioni - Miłkowska-Samul, Kamila (Studia Romanica Posnaniensia, 2020)
The aim of this paper is to address the issue of teaching politeness in textbooks dedicated to learners of Italian as a foreign language. It is assumed that in today’s ever-changing world, full of conflicts and challenges of various kinds, polite communication has become of increasing importance as it helps overcome differences between the participants of the act of communication and promote a peaceful coexistence. Politeness is a phenomenon particularly sensitive to the situational context: the forms considered appropriate vary according to the parameters such as place, channel, age or status of the interactants. Since the complexity of politeness and the variability of its exponents make it difficult to teach, the purpose of this research is to analyze if and how the current textbooks of Italian deal with this aspect of communicative competence. The paper examines which aspects of politeness are taught and with what methods. The analysis is based on the selected textbooks of Italian published in Italy and Poland, in order to compare their approaches.